The effects of probiotic supplementation on cardiometabolic health in patients with prediabetes: a systematic review, meta-analysis, and GRADE assessment - Liu, Rongfang; Wong, Gao (Frontiers in Nutrition, 2025)
IntroductionPrevious studies have yielded conflicting results regarding the effect of probiotics on prediabetes. To address this, we did an updated systematic review and meta-analysis of existing studies to evaluate the effects of probiotics on prediabetes.MethodsWe conducted a thorough search for pertinent trials on the impact of probiotic supplementation on prediabetes using various databases such as PubMed, Medline, and Google Scholar.ResultsTen RCTs were included. Probiotic supplementation significantly reduced HbA1c (WMD = −0.11; 95% CI: −0.18, −0.04; p < 0.001; I2 = 0.0%) and increased HDL-C (WMD: 2.37; 95% CI: 1.02, 3.71; p < 0.001; I2 = 0.0%). Moreover, there were no significant effects of probiotic supplementation on FBS, insulin, HOMA-IR, LDL-C, TC, TG, BMI, SBP, and DBP. GRADE assessment showed high for HbA1c and HDL-C and moderate for BMI, SBP, DBP, insulin, HOMA-IR, TC, and LDL-C, and low for FBS and TG.ConclusionProbiotic supplementation reduces HbA1c levels and increases HDL-C in individuals with prediabetes. Future research involving large-scale, international RCTs is essential to further validate its therapeutic potential.